2019
DOI: 10.1021/acs.jafc.9b03855
|View full text |Cite
|
Sign up to set email alerts
|

180 Day Repeated-Dose Toxicity Study on Forchlorfenuron in Sprague–Dawley Rats and Its Effects on the Production of Steroid Hormones

Abstract: Forchlorfenuron (FCF) is a synthetic plant cytokine-like growth regulator that is massively used in agriculture to increase fruit size and weight. There is an insufficiency of published data on the safety profile of FCF, especially as it is involved in ovarian function. In our study, a chronic toxicity study on FCF was conducted and designed by feeding at dosage levels of 0, 0.6, and 60 mg/kg body weight in Sprague–Dawley rats for 180 days. During the 180 day FCF administration, no biologically relevant change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…There have been many residue studies on CPPU itself, among which Sharma et al studied CPPU residues in grapes, as well as in environmental samples from soil and water . Much progress has been made toward the quick and accurate quantification of CPPU in fruits and vegetables. , In addition, hyperspectral imaging technology and hand-held detector have been developed that can be used to nondestructively distinguish between CPPU treated and untreated kiwifruit. , Repeated-dose toxicity study of CPPU in rats indicate the danger that CPPU has potential adverse effects on the ovaries and steroid production . In addition, animal studies in zebrafish indicate that CPPU adversely affects cardiac morphology and function …”
Section: Introductionmentioning
confidence: 99%
“…There have been many residue studies on CPPU itself, among which Sharma et al studied CPPU residues in grapes, as well as in environmental samples from soil and water . Much progress has been made toward the quick and accurate quantification of CPPU in fruits and vegetables. , In addition, hyperspectral imaging technology and hand-held detector have been developed that can be used to nondestructively distinguish between CPPU treated and untreated kiwifruit. , Repeated-dose toxicity study of CPPU in rats indicate the danger that CPPU has potential adverse effects on the ovaries and steroid production . In addition, animal studies in zebrafish indicate that CPPU adversely affects cardiac morphology and function …”
Section: Introductionmentioning
confidence: 99%
“…Because of the very low concentrations of CPPU applied, residue of CPPU in the fruit flesh is generally below the maximum residue limit (MRL; Chen et al, 2013;Li et al, 2020). However, the potential health risk of CPPU is still under evaluation (Bu et al, 2019). Available reports have shown that the dissipation rate of CPPU residue in fruit differs greatly among species (Zhang et al, 2011;Chen et al, 2013;Li et al, 2020).…”
Section: Dynamics Of Cppu Residue In the Pericarp And The Arilmentioning
confidence: 99%
“…In practice, CPPU is generally applied at very low concentration due to its strong cytokinin activity, and residue of CPPU in the fruit flesh is generally below maximum residue limit (MRL; Chen et al, 2013;Li et al, 2020). However, the potential health risk of CPPU is still under evaluation (Bu et al, 2019). Therefore, in this study, residues of CPPU in the pericarp and aril tissues were analyzed following application to provide reference about food safety related to preharvest application of CPPU.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [ 7 , 8 ] found that CPPU can induce cardiac morphology deformation and validated the cardiotoxicity of CPPU in a different experimental model. A chronic toxicity study on CPPU revealed its potentially negative effects on the ovaries [ 9 ]. In addition, long-term exposure to CPPU can induce acute and chronic intoxication and irritation to the eyes and skin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%